Analisis Pengaruh Kebijakan Harga Kebutuhan Pokok Terhadap Indeks Harga Kebutuhan Pokok Di Propinsi Jawa Timur Pasca Lumpur Lapindo - Agung Listiadi (Bisnis dan Manajemen, 2010)
During five year come East Java of growth of mean industry of pertahun will be able to reach 9%, where industrial sector expected can give contribution 27,47% from economic structure exist in East Java. And problem which related to requirement of society fundamental very sensitif, Therefore. How Influence Of Policy Of Price Requirement of specified by Fundamental is Government to Price Index storey;level Requirement of Fundamental in Province East Java of pasca Mud disaster of Lapindo ?. This research use approach of deskriptif-kuantitatif. Pursuant to calculation of price index , hence can know that in the year 2006 semester 2 happened increase of price of sembako equal to 4,31% from [his/its] elementary year. From calculation of price index , hence at in the year 2007 semester 1 increase of price sembako is that happened compared to his/its elementary year that is equal to 6,26%. Pursuant to calculation of this price index, hence can know that in the year 2007 semester 1 happened increase of price of sembako equal to 1,86% from year 2006 semester 2. From result of variable regresi of X is to policy of governmental price and for the variable of Y is price going into effect made an index to market is price for year 2006 Semester 1 got by Y = - 44,67 . And for the year of its 2006 2 equation semester of him Y = - 285,09 + 1,09X. While for the year of its 2007 1 result semester of him of Y = 254,15 + 1,06X. Shall be governmental control price of sembako marketing by performing a more intensive market operation. Government have to cope to arrest;detain fastly of increase of price of sembako by answering the demand [of] stock supply of sembako either through EOQ and also of JIT, by improve;repairing management of BULOG.